Methane Gas Hydrate - Demirbas, Ayhan; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
Climate change, environmental impact and declining natural resources are driving scientific research and novel technical solutions. Green Energy and Technology serves as a publishing platform for scientific and technological approaches to "green" - i.e., environmentally friendly and sustainable - technologies. While the main focus lies on energy and power supply, the series also covers green solutions in industrial engineering and engineering design. Green Energy and Technology is a monograph series addressing researchers, advanced students and technical consultants, as well as decision makers in industry and politics. The level presentation ranges from instructional to highly technical. Gas hydrates are potentially one of the most important energy resources for the future. They represent one of the world’s largest untapped reservoirs of energy and, according to some estimates, have the potential to meet global energy needs for the next thousand years. Methane Gas Hydrate examines this potential by focusing on methane gas hydrate, which is increasingly considered a significant source of energy. Methane Gas Hydrate gives a general overview of natural gas, before delving into the subject of gas hydrates in more detail and methane gas hydrate in particular. As well as discussing methods of gas production, it also discusses the safety and environmental concerns associated with the presence of natural gas hydrates, ranging from their possible impact on the safety of conventional drilling operations to their influence on Earth’s climate. Methane Gas Hydrate is a useful reference on an increasingly popular energy source. It contains valuable information for chemical engineers and researchers, as well as for postgraduate students.
Natural Gas -- Gas Hydrates -- Methane Gas Hydrate: as a Natural Gas Source -- Processes for Methane Production from Gas Hydrates.
Keywords: Renewable energy resources; Biochemical engineering; Environmental engineering; Biotechnology; Renewable and Green Energy; Biochemical Engineering; Environmental Engineering/Biotechnology.; Renewable and Green Energy